Some observations on the Tenant Right of Ulster - Dobbs, Conway E. (Statistical and Social Inquiry Society of Ireland, 1849)
In calling the attention of this society to a subject so much discussed, as the Tenant Right of Ulster, I wish to do so, principally with reference to that argument that is so commonly put forward, namely, that the comparative peace and prosperity of the province of Ulster, are conclusive proofs of the value of that custom, and should be considered as placing beyond dispute, the merits and the benefits conferred by it.
Read February 19th 1849
Keywords: Tenant Right of Ulster; Manufacturing industry; 314.15